Women Writers and Nineteenth-Century Medievalism - Saunders, Clare Broome. author. aut Link
XIII, 230 p.
Keywords: Saunders uniquely explores how women poets, biographers, historians, and visual artists used medieval motifs, forms, and settings to enable them to comment more freely on controversial contemporary issues, such as war and gender roles.